2018
DOI: 10.5539/ijef.v10n11p149
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Size of the Government Expenditure: An Empirical Study on Bangladesh

Abstract: Analysis of the nature of government expenditure constitutes a central concern in economic literature. This is because many countries of the world consistently have increased the size of government expenditure. Bangladesh has done the same practice over the last few decades. There is a need to investigate the factors which determine the size of the public spending of Bangladesh. The error correction modeling technique for the short-run dynamic equation and ordinary least square (OLS) for long-run static equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The results showed that the growth rate of national income and private investment significantly influence the size of public expenditure in the short-and long-run, but external and domestic debts influence the size of government expenditure only in the short run. By using OLS and error correction mode, Firoj et al (2018) analyzed the determinants of government expenditure in Bangladesh. They concluded that external debt, real GDP, urbanization, tax, and non-tax government revenue affect government expenditure positively, while the dependency on foreign aid and t rade openness affect it negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the growth rate of national income and private investment significantly influence the size of public expenditure in the short-and long-run, but external and domestic debts influence the size of government expenditure only in the short run. By using OLS and error correction mode, Firoj et al (2018) analyzed the determinants of government expenditure in Bangladesh. They concluded that external debt, real GDP, urbanization, tax, and non-tax government revenue affect government expenditure positively, while the dependency on foreign aid and t rade openness affect it negatively.…”
Section: Literature Reviewmentioning
confidence: 99%